Studi Eksposisi Mazmur 15:1-5; Etika Gerejawi dan Sosial dalam Teologi Praktika - Marga Diraja; Markus Suwandi; Yahyo Nehemia Suyadi (PT. Penerbit Tiga Mutiara, 2025)
Psalm 15:1-5 presents an ethical framework that integrates ritual piety and social responsibility as an authentic expression of faith before God. This study is motivated by the need to formulate a comprehensive model of Christian ethics that emphasizes not only personal morality but also social commitment within the context of practical theology. The central issue examined is how the ethical principles contained in Psalm 15 can be theologically interpreted and operationalized for ecclesial life and social praxis. Employing a qualitative theological method with an exegetical approach to the Hebrew text, this study interprets the ethical structure of Psalm 15 from a theological–moral perspective. The findings reveal three fundamental ethical axes: first, personal integrity, which affirms moral wholeness and a life aligned with the will of God; second, relational ethics, which demands the rejection of slander, injustice, and exploitation as a form of responsibility toward others; and third, moral stability, which is rooted in the holiness of God as the foundation for sustaining an ethical life. Based on these findings, the study develops a biblical ethical model that produces Ecclesial Ethics, embodied in the formation of the congregation’s moral habitus through spiritual discipline, and Social Ethics, defined as a commitment to uphold justice, integrity, and compassion in the public sphere. The novelty of this study lies in its integrative formulation that unites ecclesial and social ethics within a single transformative ethical paradigm. The study concludes that Psalm 15 provides a holistic foundation for Christian ethics in practical theology, positioning worship and social service as an inseparable unity of faith praxis.